Genetic Association, Variability and Path Studies for Yield Components and Quality Traits of High Yielding Rice (Oryza sativa L.) Genotypes - Devi, K. Rukmini; Hari, Y.; Chandra, B. Sathish; Prasad, K. Rajendra (International Journal of Bio-resource and Stress Management, 2022)
A field study was conducted during Kharif, 2017 (July–October) to evaluate seventy-one diverse genotypes for variability with regards to yield, yield components and quality traits in addition to correlation and path studies at Regional Agricultural Research station, Warangal, Telangana State, India. Estimates of variability, heritability and genetic advance as percent of mean were noted for all the traits, which revealed that high PCV (28.56%) and GCV (24.37%) values were recorded by grain yield plant-1, panicle density (28.47% and 20.06%). volume expansion ratio, filled seeds panicle-1. panicle weight, head rice recovery, plant height and days to 50% flowering which indicated selection for these traits will be effective, while high heritability coupled with genetic advance as percent of mean was recorded by days to 50% flowering (97.8% and 23.7%), kernel length after cooking (95% and 32.4%) and test weight (93.0% and 52%) respectively and these characters could be improved through selection. Hulling recovery recorded low genetic advance as percent of mean. Significant positive association was observed for grain yield plant-1 with days to 50% flowering, plant height, effective tillers, panicle density, panicle weight, filled seeds panicle-1, test weight, hulling percent, milling percent, head rice recovery and kernel length suggesting importance should be given to these characters, during selection. Path analysis showed that filled seeds panicle-1 (1.702) followed by kernel elongation ratio, panicle weight, milling percent and water uptake had direct effect of these traits on grain yield indicated their importance in determining the complex character and therefore should be kept in mind while practicing selection aimed at improving the grain yield.